1995
DOI: 10.1161/01.str.26.11.2120
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Basal Lamina Antigens Disappear During Cerebral Ischemia and Reperfusion

Abstract: The significant parallel losses of three basal lamina components, both in number and intensity, contribute to loss of microvascular integrity. These phenomena may be important for understanding cell extravasation and the hemorrhagic consequences of acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
285
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(299 citation statements)
references
References 41 publications
12
285
1
1
Order By: Relevance
“…MMPs degrade the components of the basal lamina, namely, heparan sulfate, laminin, fibronectin, and type IV collagen. During cellular stress from ischemia/hypoxia, the macromolecules of the basal lamina are reduced, presumably by the action of the ECM-degrading proteases, and loss of the matrix increases the rate of hemorrhage (Hamann et al, 1995). Pericytes are macrophage-like cells that are found next to the endothelial cells and are surrounded by basal lamina.…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 99%
“…MMPs degrade the components of the basal lamina, namely, heparan sulfate, laminin, fibronectin, and type IV collagen. During cellular stress from ischemia/hypoxia, the macromolecules of the basal lamina are reduced, presumably by the action of the ECM-degrading proteases, and loss of the matrix increases the rate of hemorrhage (Hamann et al, 1995). Pericytes are macrophage-like cells that are found next to the endothelial cells and are surrounded by basal lamina.…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 99%
“…The TJPs include zona occludens (ZOs) proteins in the endothelial cells, while in the endothelial cell clefts are found occludin and claudins (Furuse et al, 1993(Furuse et al, , 1998Morita et al, 1999a;Nitta et al, 2003). Proteases of the serine and matrix metalloproteinase (MMP) gene families have been shown to degrade proteins of the basal lamina around the cerebral blood vessels (Hamann et al, 1995;Fukuda et al, 2004). An earlier study showed that gelatinase B (MMP-9) degrades ZOs in focal ischemia (Asahi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Within 1-2 hours after MCAO, in the non-human primate, significant changes in laminin, collagen IV, FN, and perlecan occur within microvessel basal lamina matrix in the ischemic core. 1,2 Knowing how acute changes in microvessel matrix architecture occur quantitatively, the contributions of individual matrix proteases, and their specific cell sources are central to devising methods for preservation of microvessel and neurovascular unit integrity, and for reducing hemorrhagic transformation. 1,26 These studies were prompted by the observation in the non-human primate of acute cathepsin L protein and activity expression in the neurovascular unit coincident with the simultaneous disappearance of its substrates perlecan and collagen IV in the microvasculature.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the rapid appearance of cathepsin L also coincides with the loss of other microvessel ECM components in non-human primate, and the appearance of (pro-)MMP-2. 1,3 This suggests that very early during focal ischemia one or more matrix proteases may degrade perlecan, as well as the major structural components of the basal lamina ECM. In addition, cathepsins L and B are known to degrade the substrates and major ECM components collagen IV, laminin, and fibronectin (FN) in vitro.…”
Section: Introductionmentioning
confidence: 99%